The effects of personality and intention to act toward responsible environmental behavior - Pratiwi, Riska Dian; Rusdi, Rusdi; Komala, Ratna (University of Muhammadiyah Malang, 2019)
Efforts to improve environmental responsibility are still being developed partially, in fact this is the result of the interaction of various factors. This study aimed to investigate the effect of personality and intention to act of the responsible environmental behavior. This research was conducted at Senior High School Insan Cendekia Madani Boarding School in the second semester of 2017-2018 academic year. The method used were survey with quantitative-causal approach. This study used three variables i.e. personality (exogenous variable/X1), intention to act (exogenous variable/X2), and responsible environmental behavior (endogenous variable/X3). The subject were 90 students from grade XI of mathematics and science. The data analysis technique was used path analysis. Based on hypothesis test conducted, the values of the path coefficient between X1 and X2 was 0.385, X2 and X3 was 0.209, X1 and X3 through X2 was 0.08. The results showed that there was significant indirect effect of personality to responsible environmental behavior through the intention to act of Senior High School students.